Formation of Monolithic Ion-Selective Transport Media Based on “Click” Cross-Linked Hyperbranched Polyglycerol - Abrahamsson, Tobias; Poxson, David J.; Gabrielsson, Erik O.; Sandberg, Mats; Simon, Daniel T.; Berggren, Magnus (Frontiers in Chemistry, 2019)
In the emerging field of organic bioelectronics, conducting polymers and ion-selective membranes are combined to form resistors, diodes, transistors, and circuits that transport and process both electronic and ionic signals. Such bioelectronics concepts have been explored in delivery devices that translate electronic addressing signals into the transport and dispensing of small charged biomolecules at high specificity and spatiotemporal resolution. Manufacturing such “iontronic” devices generally involves classical thin film processing of polyelectrolyte layers and insulators followed by application of electrolytes. This approach makes miniaturization and integration difficult, simply because the ion selective polyelectrolytes swell after completing the manufacturing. To advance such bioelectronics/iontronics and to enable applications where relatively larger molecules can be delivered, it is important to develop a versatile material system in which the charge/size selectivity can be easily tailormade at the same time enabling easy manufacturing of complex and miniaturized structures. Here, we report a one-pot synthesis approach with minimal amount of organic solvent to achieve cationic hyperbranched polyglycerol films for iontronics applications. The hyperbranched structure allows for tunable pre multi-functionalization, which combines available unsaturated groups used in crosslinking along with ionic groups for electrolytic properties, to achieve a one-step process when applied in devices for monolithic membrane gel formation with selective electrophoretic transport of molecules.